CuBr-Catalyzed One-Pot Three-Component Synthesis of Novel 2-(Carbazolyl)benzothiazoles - Meesala, Ramu; Lee, Yean Kee; Arshad, Ahmad Saifuddin Mohamad; Abdullah, Iskandar; Mordi, Mohd Nizam; Abd Rahman, Noorsaadah (Synlett, 2020)
A facile synthesis of various 2-(carbazolyl)benzothiazoles has been developed by one-pot CuBr-catalyzed three-component reactions of 2-iodoanilines, arylaldehydes, and elemental sulfur. Unlike traditional approach, this reaction exhibited a good functional group tolerance to produce the corresponding 2-(carbazolyl)benzothiazoles in good yields in the absence of any additive.
Keywords: 2-(carbazolyl)benzothiazoles; 2-iodoanilines; arylaldehydes; elemental sulfur